AKTUALISASI PENDIDIKAN NILAI DAN MORAL PADA SISWA SEKOLAH DASAR MELALUI MEDIA PEMBELAJARAN BERBASIS PERMAINAN WORDWALL - Triaswari, Finanda Dwi; Sutrisno, Sutrisno; Adiyaksa, Wily; Ayu Rustiya, Sela (Universitas Muhammadiyah Ponorogo, 2023)
The purpose of this study was to find out how the model of inculcating value and moral education in elementary school students through game-based learning media called wordwall. The research method used is qualitative research with a case study approach, using interview and observation instruments. The results of this study describe the moral values of elementary school children that need to be improved again. At any level of education, especially basic education. Because elementary school education is the main foundation for Indonesia's young generation. Students are identical with the world of play, so the suitable media is media that contains elements of the game. In line with that, the media that can be used for interactive learning is Wordwall. This website-based application can be used to create learning media such as quizzes, match, pair, word random, word search, grouping. This Wordwall learning media was created with the aim of providing knowledge and instilling what and how these moral values are in elementary school children in everyday life. The method used in this research is observation or survey. The results of this study describe the moral values of elementary school children that need to be improved again.